Embodied energy and cost of building materials: correlation analysis. Issue 5 (4th July 2017) - Dixit, Manish K.
ABSTRACT: The US building sector consumes 48% of the nation's annual energy as operating and embodied energy. Calculating embodied energy is difficult, complex and more resource-consuming than calculating operating energy due to a lack of complete, accurate and specific embodied energy data. One commonly used method to calculate embodied energy is input–output-based (IO) analysis, which utilizes economic data. The use of economic data indicates some relationship between embodied energy and cost. Some studies have investigated whether the embodied energy of a building can be predicted from its cost. These studies analyzed the relationship of the cost and embodied energy of a building and found a strong, positive correlation. However, when analyzed at the material level, the correlation weakened. This paper develops an improved input–output-based hybrid (IOH) model to calculate the complete, accurate and material-specific embodied energy of 21 commonly used building materials. After calculating and evaluating the embodied energy, the correlation of the embodied energy and cost of materials was analyzed. The results demonstrate a very strong and positive correlation between embodied energy and cost. In conclusion, more research may be required to predict embodied energy from cost data.